Configuration vs. attractors and others : accounting for variation in pedestrian movement densities in Qiaym Street and Emam Street, Yazd City, Iran - Mahboubeh Rakhshanifar, 1985-; Loon, Wai Chau, supervisor; Fakulti Alam Bina (2011)
Thesis (Sarjana Sains (Rekabentuk Bandar)) - Universiti Teknologi Malaysia, 2011